An evaluation of completed and averted school shootings - Winch, Ashley T.; Alexander, Kristi; Bowers, Clint; Straub, Frank; Beidel, Deborah C. (Frontiers in Public Health, 2024)
Introduction For over two decades school shootings have become a significant concern, especially in the United States. Following a rampage school shooting, extensive resources are devoted to gathering all of the information surrounding the event. To date, few studies have compared completed to averted, or near-miss, school shootings. This study utilized the largest known sample of cases based in the United States in an effort to identify potential targets for prevention. Method Data were derived from the Averted School Violence database of incidents occurring between 1999 and 2020. Statistical analyses were conducted to determine how age, co-conspirator involvement, engagement in leakage warning behavior, and motives – in isolation and in combination – varied between groups. Results In insolation, age, co-conspirator involvement, engagement in leakage warning behaviors, and motives were significantly different between groups. However, when these variables were combined into a logistic regression, co-conspirator involvement, engagement in leakage warning behaviors, and motives involving suicidal intent emerged as statistically significant predictors of group membership. Age no longer differentiated the two types of events. Conclusion This study demonstrates that regardless of suspect age, threats of school violence must be taken seriously and investigated fully. Further, students reporting their peers’ engagement in shooting-related behaviors (e.g., bringing a gun to school, mapping school, etc.) was one of the most significant predictors that a plot will be thwarted. While perpetrators who planned with others had increased odds of their plot being identified, those acting alone still demonstrated leakage behaviors. If individuals in the school environment are educated regarding warning behaviors, lone perpetrators can still be identified and reported to authorities. The perpetrator’s emotional distress, in particular depressive or suicidal thoughts were also a significant predictor of a completed school shooting. Future research efforts should focus on the development and evaluation of peer training programs to assist in the detection of school shooting warning behaviors.